Physical education in early education: An intervention program for reducing aggressive and social insecure behavior - Μουρατίδου, Κατερίνα (Επιστημονική Επετηρίδα Παιδαγωγικού Τμήματος Νηπιαγωγών Πανεπιστημίου Ιωαννίνων, 2016)
The present study aimed to examine the effect of a physical education program on the reduction of aggressive and social insecure behavior of young children. The sample comprised of 194 children, aged 4-5 years. The experimental group consisted of 99 children, while the rest 95 children formed the control group. The experimental group participated in an 8-week physical education program, based on physical activities and kinetic theatrical playing, while the control group was engaged in free-play activities during the same period. All participants completed the Checklist of Aggressive Behavior (CAB) (Petermann & Petermann, 2001) and the Checklist of Social Insecure Behavior (CSIB) (Petermann & Petermann, 2003). The results revealed that the experimental group exhibited statistically lower aggressive and social insecure behaviors after the intervention compared to the control group. These findings indicate that an appropriate design of physical education could support social development in early childhood.